Intervenciones de enfermería en neonatos con atresia esofágica tras reparación quirúrgica: revisión sistemática - Montalvo Muñoz, Anderson Fabian (2025)
Introduction: Congenital disorders that can occur in humans are known as: congenital anomalies, malformations or congenital defects, are structural alterations, such as esophageal atresia (EA). Objective: To describe the nursing interventions applied in neonates with esophageal atresia after surgical repair, systematic review. Methodology: A systematic review was carried out for the selection and analysis of primary studies, with a qualitative and descriptive approach. A search was made in scientific databases and repositories applying inclusion and exclusion criteria, to define 80 scientific articles, using the PRISMA methodology, the selected articles were analyzed and reviewed, to define 18 articles for the final review. Results: These indicated that nursing care of neonates with EC is essential for the neonate's recovery. Pre-surgical care includes rehydration and nutritional management and post-surgical care: prevention of pneumonia, sepsis and pulmonary complications, as well as intensive respiratory surveillance, implementation of physiotherapy protocols and respiratory care by the nursing staff. Conclusion: Esophageal atresia is a significant clinical challenge for health personnel, due to the complex nature and associated complications. Early diagnosis, appropriate surgical intervention and a multidisciplinary approach are essential to improve the prognosis. Parental education and postoperative follow-up are essential to avoid long-term complications and improve quality of life.